Economic Inclusion of LGBTI Groups in Thailand - World Bank Group (World Bank, Washington, DC, 2018)
Thailand is widely considered progressive among developing and middle-income countriesregarding the inclusion of lesbian, gay, bisexual, transgender, or intersex (LGBTI) people. Yet,a growing body of research shows they still experience discrimination, limited job and housingopportunities, and barriers to accessing many common services. Most information on sexual orientation and gender identity (SOGI) in Thailand is qualitative in nature. A new study led by the World Bank, in partnership with Thammasat University, Love Frankie, and the Nordic Trust Fund, includes the first endeavor to gather and analyze quantitative data on economic and financial outcomes for a large, statistically significant sample of LGBTI people in Thailand. Qualitative data from in-depth "live story" interviews with 19 SOGI-diverse participants from across each of Thailand's main regions complement the online survey data and provide further insights into the lives of LGBTI respondents. For the first time in Thailand, the study also presents information on non-LGBTI people and their attitudes toward LGBTI groups, based on survey responses from a statistically representative non-LGBTI reference group.